Performance evaluation and fouling prevention of polymeric nanofiltration membrane for treating textile dyeing wastewater - Othman, Nurhidayati (Penerbit UTM, 2007)
Textile industry is one of the oldest and heaviest polluter in the world. Nowadays, approximately half of the available water is being used for domestic purposes, and the other half is consumed by the industrial and agricultural activities. The increasing world population results in the need for more production of clothes and hence more water consumption is required for the industrial processes. In general, substantial amounts of waters, mineral salts and reactive dyes are used on an average for every kilogram of fabric produced, causing a large amount of wastewater generated from the industrial daily operation. All the effluent discharged from industry present the same problem in terms of not environmentally friendly. Thus, it is paramount important to have a proper treatment system before it is discharged into environment in order to minimize the water pollution. It is known that the loss of dyes to the effluent can interfere with the transmission of light in receiving waters, interrupting photosynthesis process and aquatic life. Moreover, the effluent which generally has a dark reddishbrown color is aesthetically unpleasing when discharged to water.